Survei Minat Masyarakat Terhadap Olahraga Tradisional Balogo di Desa Kelampaian Ilir - Rosalina, Rosalina; Kahri, Ma'ruful; Nurdiansyah, Nurdiansyah (Universitas Hamzanwadi, 2024)
This research was motivated by the unknown problem of the lack of public interest in the traditional balogo sport in Kelampaian Ilir Village. This research aims to determine the level of community interest in the traditional balogo sport in Kelampaian Ilir Village. This research method uses survey research with a quantitative descriptive approach. The population in this study was the people of Kelampaian Ilir Village, totaling 1688 people and the research sample was 196 respondents. Sampling used random sampling technique. The instrument used in the research was a questionnaire. Data collection techniques used descriptive percentage techniques, validity tests, reliability tests and analysis using Microsoft Excel and SPSS version 23. The results of research on community interest in the traditional balogo sport in Kelampaian Ilir Village were categorized as very high, 0 respondents or 0%, in the high category there were 42 respondents or 21.43%, in the medium category there were 105 respondents or 53.57%, in the low category there were 25 respondents or 12.76%, and in the very low category there were 24 respondents or 12.24%. So it can be said that the public's interest in traditional balogo sports in Kelampaian Ilir Village is in the medium category